FAKTOR-FAKTOR PENDORONG TERBENTUKNYA ORIENTASI PASAR EKSPOR BATIK JAMBI - Ade Octavia (Jurnal Dinamika Manajemen, 2013)
This study aim is to determine the effect of customer orientation, marketing mix, capability, competitive advantage on export marketing orientation.Data was collected through 100 respondents that adpopted survey as research method. Data collection using questionnaire and then the data were analyzed using SEM tools. The study found that competitive advantage positive effect on export marketing orientation. Moreover,customer orientation and marketing mix have a significant indirect effect on export marketing orientation. Keywords:Â customer orientation, marketing mix,capability, competitive advantage ,export marketing orientation